Lithium iron phosphate positive electrode material and preparation method and application thereof

By in-situ doping lithium iron phosphate and composited with chiral carbon, and coating the surface with copper selenide and chiral carbon and graphene oxide layers, the problem of low conductivity and diffusion efficiency of lithium iron phosphate positive electrode material is solved, significantly improving its rate performance and cycling stability.

CN119822346AInactive Publication Date: 2025-04-15HUBEI RUIPAI NEW ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510025990.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have low electronic conductivity and ion diffusion efficiency, resulting in poor performance and long-term charge and discharge performance.

Method used

By doping lithium iron phosphate in situ, sodium ions occupy the lithium position and magnesium ions occupy the iron position. The doped modified lithium iron phosphate is composited with chiral carbon material, and the material surface is coated with a composite layer of copper selenide and chiral carbon and graphene oxide.

Benefits of technology

It improves the ion mobility of lithium ions, improves the cyclic stability of the material, reduces resistance, enhances the conductivity and wetting properties, thereby improving the rate performance and long-term charge and discharge performance of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232721100000071
    Figure BDA0005232721100000071
  • Figure BDA0005232721100000081
    Figure BDA0005232721100000081
  • Figure BDA0005232721100000082
    Figure BDA0005232721100000082
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to a lithium iron phosphate positive electrode material and a preparation method and application thereof.The preparation method comprises the following steps that 1, a lithium source, a sodium source, a magnesium source, an iron source and a phosphorus source are mixed to form a mixture, then a dispersing agent and an antioxidant are added, and the mixture is evenly mixed to obtain a mixed solution, performing hydrothermal reaction on the mixed solution to obtain a doped lithium iron phosphate precursor; 2) carrying out ball-milling mixing on an organic chiral material and the lithium iron phosphate precursor, and then carrying out high-temperature treatment in the presence of shielding gas to obtain a precursor A; 3) adding a copper source, a selenium source, alkali and a reducing agent into a solvent to obtain a mixed solution, and then adding the mixed solution into the precursor A for reaction to obtain a precursor B; and 4) in the presence of an initiator, carrying out polymerization reaction on the precursor B, graphene oxide, a chiral modifier and a monomer to obtain the lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material provided by the invention can effectively improve the cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In the related technology, lithium-ion batteries have become an ideal power source for existing electronic products due to their advantages such as high operating voltage, high energy density, low self-discharge rate, stability and environmental protection. At present, the positive electrode materials of lithium-ion batteries mainly include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide and lithium iron phosphate. Among them, lithium iron phosphate (LiFePO4) has the advantages of wide source, low price, good thermal stability, non-hygroscopicity and environmental friendliness, and has attracted widespread attention. LiFePO4 is a slightly distorted hexagonal closest packing structure belonging to the Pmm space group. The crystal is composed of FeO6 octahedron and PO4 tetrahedron to form a spatial skeleton. P occupies the tetrahedral position, while Fe and Li are filled in the gaps of the octahedron. In the lattice, FeO6 is connected by the common angle of the bc plane, and LiO6 forms a long chain with common edges along the b axis. One of the FeO6 octahedrons shares an edge with two LiO6 octahedrons, and each PO4 group has one common edge and two common edges with the FeO6 octahedron and LiO6 octahedron, respectively. Since there is no continuous FeO6 edge-sharing octahedral network, electronic conduction cannot be formed. At the same time, the PO4 tetrahedron limits the volume change of the lattice, making the Li + The deintercalation and electron diffusion are affected, resulting in lower electronic conductivity and ion diffusion efficiency of the LiFePO4 positive electrode material. Summary of the invention

[0003] The present invention aims to solve at least one of the above-mentioned technical problems in the prior art to a certain extent, so as to give full play to the advantages of lithium iron phosphate materials, such as wide sources, low prices, good thermal stability, non-hygroscopicity and environmental friendliness.

[0004] In order to achieve the above object, the present invention provides a first aspect of a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0005] 1) mixing a lithium source, a sodium source, a magnesium source, an iron source and a phosphorus source to form a mixture, then adding a dispersant and an antioxidant, mixing evenly to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction to obtain a doped lithium iron phosphate precursor;

[0006] 2) ball-milling the organic chiral material and the lithium iron phosphate precursor, and then subjecting the mixture to high-temperature treatment in the presence of a protective gas to obtain a precursor A;

[0007] 3) adding a copper source, a selenium source, an alkali, and a reducing agent into a solvent to obtain a mixed solution, and then adding the mixed solution into the precursor A to react and obtain a precursor B;

[0008] 4) In the presence of an initiator, the precursor B, graphene oxide, chiral modifier and monomer are polymerized to obtain a lithium iron phosphate positive electrode material.

[0009] The second aspect of the present invention provides a lithium iron phosphate positive electrode material prepared according to the above-mentioned preparation method. Specifically, the lithium iron phosphate positive electrode material includes a core, a first coating layer and a second coating layer from the inside to the outside, the core is a composite material of sodium-magnesium co-doped lithium iron phosphate and chiral carbon; the first coating layer is cuprous selenide; the second coating layer is a composite material of chiral carbon and graphene oxide.

[0010] The third aspect of the present invention also provides the use of the above-mentioned lithium iron phosphate positive electrode material in a lithium ion battery.

[0011] Through the above technical solution, the present invention has the following technical effects:

[0012] 1) By in-situ doping of lithium iron phosphate, sodium ions occupy the lithium site and magnesium ions occupy the iron site, which is beneficial to reduce the binding strength of lithium-oxygen bonds and broaden the lithium ion diffusion channel, thereby improving the ion mobility of lithium ions; at the same time, due to the doping of lithium iron phosphate, the lattice defects in the lithium iron phosphate are increased, which affects the stability of the lithium iron phosphate lattice structure, and further affects the rate performance and long-term charge and discharge performance of the lithium iron phosphate material; by compounding the doped and modified lithium iron phosphate with a chiral carbon material, the cycle stability of the lithium iron phosphate material can be improved.

[0013] 2) Cuprous selenide has good electrical conductivity. By coating a layer of cuprous selenide coating on the surface of the lithium iron phosphate precursor, the conductivity of the material can be improved and the resistance of the composite material can be reduced. At the same time, it can also solve the iron dissolution phenomenon of the composite material during the cyclic charge and discharge process and reduce the occurrence of side reactions.

[0014] 3) The chiral carbon and graphene oxide coating layers are constructed on the outermost layer of the composite material, which can further improve the conductivity of the composite material and improve the wettability of the positive electrode material and the electrolyte. In addition, graphene oxide has a large interlayer spacing and conjugated carbon bond system. Combined with the helical structure of the chiral polymer, it can provide longitudinal and lateral transmission channels for lithium ions, increase the reaction active sites, and reduce the volume expansion of lithium iron phosphate, thereby improving the cycle stability of the positive electrode material.

[0015] Other features and advantages of the embodiments of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0016] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0019] 1) mixing a lithium source, a sodium source, a magnesium source, an iron source and a phosphorus source to form a mixture, then adding a dispersant and an antioxidant, mixing evenly to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction to obtain a doped lithium iron phosphate precursor;

[0020] 2) ball-milling the organic chiral material and the lithium iron phosphate precursor, and then subjecting the mixture to high-temperature treatment in the presence of a protective gas to obtain a precursor A;

[0021] 3) adding a copper source, a selenium source, an alkali, and a reducing agent into a solvent to obtain a mixed solution, and then adding the mixed solution into the precursor A to react and obtain a precursor B;

[0022] 4) In the presence of an initiator, the precursor B, graphene oxide, chiral modifier and monomer are polymerized to obtain a lithium iron phosphate positive electrode material.

[0023] The present invention firstly performs in-situ doping on lithium iron phosphate, wherein sodium ions occupy the lithium site and magnesium ions occupy the iron site, which is beneficial to reducing the binding strength of lithium-oxygen bonds and widening the lithium ion diffusion channel, thereby improving the ion mobility of lithium ions; at the same time, due to the doping of lithium iron phosphate, the lattice defects in the lithium iron phosphate are increased, which affects the stability of the lithium iron phosphate lattice structure, and further affects the rate performance and long-term charge and discharge performance of the lithium iron phosphate material; by compounding the doped and modified lithium iron phosphate with a chiral carbon material, the cycle stability of the lithium iron phosphate material can be improved.

[0024] Under preferred conditions, in step 1), the molar ratio of the lithium source, sodium source, magnesium source, iron source and phosphorus source is: 1: (0.01-0.1): (0.05-0.3): (0.95-1.2): (0.95-1.2).

[0025] In the present invention, the doped lithium iron phosphate can be prepared by a hydrothermal method. Specifically, the conditions of the hydrothermal reaction include: a temperature of 120-200° C. and a time of 4-10 hours.

[0026] In the present invention, by mixing the doped lithium iron phosphate material with the chiral organic material and then subjecting it to high temperature treatment, the precursor A that can be generated is a composite of chiral carbon-doped lithium iron phosphate material, which can improve the cycle performance of doped lithium iron phosphate. Under preferred conditions, the organic chiral material is a chiral compound of C6-C15, and illustratively, the chiral compound is selected from at least one of L-diethyl tartrate, L-glucose, L-α-methylbenzylamine, L-mannitol, L-cis-3-aminocyclohexanecarboxylic acid, L-sorbitol, L-camphorsulfonic acid, and L-dopamine. This is because if the carbon chain of the organic chiral material is too short, it can only form carbon particles on the surface of lithium iron phosphate after carbonization, and thus the volume expansion of lithium iron phosphate cannot be effectively suppressed, and the cycle performance of the battery cannot be effectively improved. Further preferably, in step 2), the mass ratio of the organic chiral material to the lithium iron phosphate precursor is (0.1-0.5): 1.

[0027] According to the present invention, in step 2), the conditions of the high temperature treatment include: a temperature of 400-600° C. and a time of 2-8 hours.

[0028] Cuprous selenide has good electrical conductivity. In the present invention, by coating a cuprous selenide coating layer on the surface of the lithium iron phosphate precursor, the electrical conductivity of the material can be improved and the resistance of the composite material can be reduced. At the same time, the iron dissolution phenomenon of the composite material during the cyclic charge and discharge process can be solved and the generation of side reactions can be reduced. In step 3), the amount ratio of the copper source, the selenium source and the precursor A is (1-4) mmol: (0.5-2) mmol: 1 g.

[0029] Further preferably, in step 3), the solvent is selected from triethylene glycol; and the reaction conditions are: temperature of 200-280° C. and time of 1-8 h.

[0030] In the present invention, a chiral carbon and graphene oxide coating layer is constructed on the outermost layer of the composite material, which can further improve the conductivity of the composite material and improve the wettability of the composite positive electrode material with the electrolyte. In addition, graphene oxide has a large interlayer spacing and a conjugated carbon bond system. Combined with the helical structure of the chiral polymer, it can provide longitudinal and lateral transmission channels for lithium ions and increase the reaction active sites; it can also reduce the volume expansion of lithium iron phosphate, thereby improving the cycle stability of the positive electrode material.

[0031] Under preferred conditions, in step 4), the chiral modifier is selected from at least one of L-2-aminobutane, L-2-methylpyrrolidine, L-tartaric acid, L-malic acid and L-lactic acid.

[0032] Further preferably, in step 4), the monomer is selected from at least one of pyrrole, aniline, acetylene and thiophene.

[0033] It should be noted that in the present invention, the ratio of chiral carbon to graphene oxide should be controlled within a reasonable range to construct effective longitudinal and transverse lithium ion transmission channels. Under preferred conditions, in step 4), the mass ratio of the chiral modifier, the graphene oxide and the monomer is (0.1-0.3): (0.3-1.5): 1.

[0034] Further preferably, the mass ratio of the precursor B to the monomer is 1:(0.2-1).

[0035] The present invention also provides a lithium iron phosphate positive electrode material prepared according to the above preparation method; specifically, the lithium iron phosphate positive electrode material includes a core, a first coating layer and a second coating layer from the inside to the outside, the core is a composite material of sodium-magnesium co-doped lithium iron phosphate and chiral carbon; the first coating layer is cuprous selenide; the second coating layer is a composite material of chiral carbon and graphene oxide.

[0036] The present invention also provides application of the lithium iron phosphate positive electrode material in a lithium ion battery.

[0037] The present invention is described in detail below by way of examples.

[0038] Example 1

[0039] 1. Preparation of lithium iron phosphate positive electrode material:

[0040] Lithium hydroxide, sodium hydroxide, magnesium chloride and ferric chloride are dissolved in water, and then phosphoric acid is added to the solution under stirring until the pH value of the mixed solution is 6, and then 0.05wt% of hexadecyltrimethylammonium chloride and 1wt% of ascorbic acid are added to the mixed solution and stirred to mix evenly to obtain a mixed solution. + 、Na + Mg 2+ , Fe 3+ and PO4 3+ The molar ratio of is: 1:0.03:0.1:1:1, then the mixed solution is transferred into a reactor and reacted at 160°C for 6 hours. After the reaction is completed and cooled to room temperature, the product is centrifuged and washed to obtain sodium and magnesium co-doped lithium iron phosphate, referred to as doped lithium iron phosphate precursor;

[0041] 2) 1 g of L-diethyl tartaric acid and 10 g of lithium iron phosphate precursor were ball-milled in a planetary ball mill for 60 min, and then the obtained mixture was placed in a tube furnace, and argon gas was continuously introduced into the tube furnace, followed by high-temperature treatment at 500° C. for 3 h to obtain precursor A;

[0042] 3) 20 mmol of copper chloride, 10 mmol of selenium dioxide, 40 mmol of sodium hydroxide and 50 mmol of ascorbic acid were mixed in 250 mL of triethylene glycol, and then 10 g of precursor A was added and mixed evenly, and then reacted at 240° C. for 120 min in an oil bath under stirring conditions. After the reaction was completed, the system was naturally cooled to room temperature, and the precipitate was centrifuged and washed to obtain precursor B;

[0043] 4) 1 g of L-tartaric acid, 5.2 mL (5 g) of pyrrole, and 2.5 g of graphene oxide were added to 150 mL of ethanol solution and stirred to mix, then 10 g of precursor B was added and stirring was continued for 30 min, and then ammonium persulfate was added to react for 12 h, and the product was filtered and washed to obtain a lithium iron phosphate positive electrode material.

[0044] 2. Preparation of lithium-ion batteries

[0045] The lithium iron phosphate positive electrode material, carbon black and PVDF were mixed evenly in a mortar at a mass ratio of 8:1:1, and NMP was added for homogenization for 30 minutes to obtain a slurry. The slurry was evenly coated on an aluminum foil, and then dried, rolled and sliced ​​to obtain a positive electrode sheet.

[0046] The positive electrode was placed in a glove box for assembly of a 2032-type button cell. The negative electrode was a lithium sheet. The electrolyte used was a mixture of 1 mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC). The diaphragm was Celgard 2325. The diaphragm was soaked, and then the electrode was placed on top of the diaphragm. Finally, the gasket and the shrapnel were stacked on the surface of the electrode in sequence. After completion, the positive electrode shell was used to cover it and the battery sealing device was used to seal it. The packaged battery was left to stand for 12 hours and then its electrochemical performance was tested. The experimental results are shown in Table 1.

[0047] The powder resistivity was measured by the four-probe method.

[0048] Examples 2-3 and Comparative Examples 1-2

[0049] The method of Example 1 is followed, except that the mass ratio of the organic chiral material L-diethyl tartrate (L-DET) and lithium iron phosphate (LFP) is as shown in Table 1.

[0050] Table 1

[0051]

[0052] It can be concluded from Table 1 that the specific capacity of the battery increases with the increase in the proportion of the organic chiral material L-tartrate diethyl ester (L-DET). However, when the proportion of L-tartrate diethyl ester (L-DET) increases to 0.2 of the lithium iron phosphate material, continuing to increase the proportion of L-DET reduces the specific capacity of the battery. At the same time, the battery's first coulombic efficiency and the capacity retention rate after 200 cycles also decrease. The possible reason is that the increase in the amount of chiral organic material leads to an increase in the carbon content in the core after high-temperature treatment, which leads to a decrease in the performance of the battery.

[0053] Example 4 and Comparative Examples 3-5

[0054] The method of Example 1 is followed, except that the types of organic chiral materials are as shown in Table 2.

[0055] The chiral organic material is a C6-C15 chiral compound, and the chiral compound is selected from at least one of L-diethyl tartrate, L-glucose, L-α-methylbenzylamine, L-mannitol, L-cis-3-aminocyclohexanecarboxylic acid, L-sorbitol, L-camphorsulfonic acid, and L-dopamine.

[0056] Table 2

[0057]

[0058] It can be seen from Table 2 that when the carbon chain length of the organic chiral material is greater than 6, the discharge capacity and cycle performance of the lithium battery can be effectively improved, and the resistivity of the material can be reduced. However, when the carbon chain of the organic chiral material is too short, that is, when the carbon chain length is less than 6, although the performance of the material can be improved to a certain extent, the improvement in performance is limited.

[0059] Examples 5-6 and Comparative Examples 6-7

[0060] The method of Example 1 is followed, except that: Cu 2+ 、Se 2+ The ratio to precursor A is shown in Table 3.

[0061] Table 3

[0062]

[0063]

[0064] It can be seen from Table 3 that by coating a layer of cuprous selenide on the surface of precursor A, the resistivity of the lithium iron phosphate powder material can be reduced, and the resistivity of the lithium iron phosphate positive electrode material decreases with the increase of cuprous selenide content, but at the same time, the specific capacity and the first coulombic efficiency of the battery gradually decrease. Therefore, Cu is preferred in this application. 2+ :Se 2+: The ratio of precursor A is 2mmol:1mmol:1g.

[0065] Examples 7-11 and Comparative Examples 8-11

[0066] The method of Example 1 is followed, except that the mass ratios of L-tartaric acid (L-TA), graphene oxide (RGO) and pyrrole are as shown in Table 4, and the experimental results are as shown in Table 4.

[0067] Comparative Example 12

[0068] According to the method of Example 1, the difference is that in step 4), graphene oxide is not contained, and the specific steps are as follows:

[0069] 1.42 g of L-tartaric acid and 7.08 g of pyrrole were added to 150 mL of ethanol solution and stirred to mix. Then, 10 g of precursor B was added and stirring was continued for 30 min. Then, ammonium persulfate was added and reacted for 12 h. The product was filtered and washed to obtain a lithium iron phosphate positive electrode material. The experimental results are shown in Table 4.

[0070] Comparative Example 13

[0071] According to the method of Example 1, the difference is that in step 4), L-tartaric acid is not contained, and the specific steps are as follows:

[0072] 6 g of pyrrole and 2.5 g of graphene oxide were added to 150 mL of ethanol solution and stirred to mix. Then, 10 g of precursor B was added and stirring was continued for 30 min. Then, ammonium persulfate was added to react for 12 h. The product was filtered and washed to obtain a lithium iron phosphate positive electrode material. The experimental results are shown in Table 4.

[0073] Comparative Example 14

[0074] According to the method of Example 1, the difference is that in step 4), L-tartaric acid and pyrrole are not contained, and the specific steps are as follows:

[0075] 8.5 g of graphene oxide was added to 150 mL of ethanol solution and stirred to mix. Then, 10 g of precursor B was added and stirring was continued for 30 min. Then, ammonium persulfate was added and reacted for 12 h. The product was filtered and washed to obtain a lithium iron phosphate positive electrode material. The experimental results are shown in Table 4.

[0076] Table 4

[0077]

[0078] The possible reasons are: graphene oxide has a larger interlayer spacing and a conjugated carbon bond system. Combined with the helical structure of the chiral polymer, it can provide longitudinal and lateral transmission channels for lithium ions, reduce the volume expansion of lithium iron phosphate, and thus improve the cycle stability of the battery.

[0079] Example 12- and Comparative Example 15

[0080] The method of Example 1 is followed, except that the mass ratio of L-tartaric acid (L-TA), graphene oxide (RGO) and pyrrole is kept unchanged, and the mass ratio of precursor B to monomer is adjusted, as shown in Table 5.

[0081] Table 5

[0082]

[0083] It can be seen from Table 5 that: with the increase of the pyrrole ratio, the content of the chiral carbon / graphene composite material coated on the surface of the precursor B also gradually increases, which can improve the conductivity of the lithium iron phosphate positive electrode material and the cycle performance of the battery. However, when the pyrrole ratio reaches 1 times the amount of precursor B, the specific capacity and capacity retention rate of the battery begin to decrease. The possible reason is that the surface of the precursor A is coated with an excessive amount of polymer, resulting in an excessive thickness of the second coating layer, which affects the performance of the battery.

[0084] It should be noted that the specific experimental steps or conditions not specified in the embodiments of the present invention can be carried out according to the conventional experimental steps or conditions described in the literature in the art. The reagents or instruments used without specifying the manufacturer are all conventional reagent products that can be obtained commercially.

[0085] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: 1) mixing a lithium source, a sodium source, a magnesium source, an iron source and a phosphorus source to form a mixture, then adding a dispersant and an antioxidant, mixing evenly to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction to obtain a doped lithium iron phosphate precursor; 2) ball-milling the organic chiral material and the lithium iron phosphate precursor, and then subjecting the mixture to high-temperature treatment in the presence of a protective gas to obtain a precursor A; 3) adding a copper source, a selenium source, an alkali, and a reducing agent into a solvent to obtain a mixed solution, and then adding the mixed solution into the precursor A to react and obtain a precursor B; 4) In the presence of an initiator, the precursor B, graphene oxide, chiral modifier and monomer are polymerized to obtain a lithium iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of the lithium source, sodium source, magnesium source, iron source and phosphorus source is 1: (0.01-0.1): (0.05-0.3): (0.95-1.2): (0.95-1.2); and / or The conditions of the hydrothermal reaction include: temperature of 120-200° C. and time of 4-10 h.

3. The preparation method according to claim 1, characterized in that: In step 2), the organic chiral material is a C6-C15 chiral compound; Preferably, the chiral compound is selected from at least one of L-diethyl tartrate, L-glucose, L-α-methylbenzylamine, L-mannitol, L-cis-3-aminocyclohexanecarboxylic acid, L-sorbitol, L-camphorsulfonic acid, and L-dopamine.

4. The preparation method according to claim 3, characterized in that: In step 2), the mass ratio of the organic chiral material to the lithium iron phosphate precursor is (0.1-0.5):

1.

5. The preparation method according to claim 4, characterized in that: In step 2), the conditions of the high temperature treatment include: a temperature of 400-600° C. and a time of 2-8 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step 3), the usage ratio of the copper source, the selenium source and the precursor A is (1-4) mmol: (0.5-2) mmol: 1 g; In step 3), the solvent is selected from triethylene glycol; In step 3), the reaction conditions are: temperature of 200-280° C. and time of 1-8 h.

7. The preparation method according to any one of claims 1 to 5, characterized in that: In step 4), the chiral modifier is selected from at least one of L-2-aminobutane, L-2-methylpyrrolidine, L-tartaric acid, L-malic acid and L-lactic acid; In step 4), the monomer is selected from at least one of pyrrole, aniline, acetylene and thiophene.

8. The preparation method according to any one of claims 1 to 5, characterized in that: In step 4), the mass ratio of the chiral modifier, the graphene oxide and the monomer is (0.1-0.3): (0.3-1.5): 1; The mass ratio of the precursor B to the monomer is 1:(0.2-1).

9. A lithium iron phosphate positive electrode material prepared according to the method according to any one of claims 1 to 8; wherein The positive electrode material includes a core, a first coating layer and a second coating layer from the inside to the outside, the core is a composite material of sodium-magnesium co-doped lithium iron phosphate and chiral carbon; the first coating layer is cuprous selenide; and the second coating layer is a composite material of chiral carbon and graphene oxide.

10. Use of the lithium iron phosphate positive electrode material according to claim 9 in lithium ion batteries.

Citation Information

Patent Citations

  • Composite electrode material and application thereof

    CN107039640A

  • Lithium iron phosphate-based composite material with capacity higher than theoretical capacity of lithium iron phosphate, preparation method and use of lithium iron phosphate-based composite material

    CN108735997A

  • A preparation method of polymer-coated lithium iron phosphate cathode material

    CN109037658A

  • Modified lithium iron phosphate positive electrode material, preparation method thereof and secondary battery comprising modified lithium iron phosphate positive electrode material

    CN115799516A

  • Lithium iron phosphate composite positive electrode material and preparation method thereof

    CN116995218A

Cited By

  • High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof

    CN120664513A